The ten commandments - MacKenzie, Aeneas; De Mille, Cecil B.; Paramount (Firm) (Hollywood, Calif. : Paramount DVD, 2006)
Filmed in Egypt and the Sinai, and featuring one of the biggest sets ever constructed for a motion picture, this film tells the story of the life of Moses (Charlton Heston), who turn his back on a privileged life to lead his people to freedom
Disc 1. 1956 feature film, pt. 1 -- Disc 2. 1956 feature film, pt. 2 ; Special features ; Disc 3. 1923 silent film
Originally released as a motion picture in 1956
50th anniversary collection
Title from title screen
DVD Format
Recorded in Dolby digital 5.1 surround (English), 2.0 surround (English), and mono (French)
With English, Thai, Mandarin, Korea and Cantonese subtitles for CD 1 &2, and Thai, Korean, MAndarin and Cantonese for CD 3
Keywords: Moses -- (Biblical leader) -- Drama; Ten commandments -- Drama; Bible stories -- Drama